1997
DOI: 10.1007/s004240050490
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subsarcolemmal sodium concentration measured by Na-Ca exchanger activity during Na-pump inhibition and β-adrenergic stimulation in guinea-pig ventricular myocytes

Abstract: Measurement of Na-Ca exchange activity was used to examine subsarcolemmal sodium levels ([Na+]s) in single, voltage-clamped guinea-pig cardiac myocytes while Na-K pump activity was modulated pharmacologically. Changes in Nas were evaluated from phase-plane analysis of the changes in intracellular calcium, measured using the fluorescent indicators Fura-red and Fluo-3. Activation of beta-adrenoceptors with 1 microM isoprenaline resulted in activation of the cAMP-dependent chloride current, but had no effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
5
14
2
Order By: Relevance
“…However, this augmentation was most likely due to the activation of I CFTR-Cl , which is also sensitive to Ni 2ϩ . Our results support previous studies (2,5,13,20) and a recent report of studies of rabbit ventricular cells by Ginsburg and Bers (11). Using guinea pig ventricular cells, Perchenet et al (25) and Zhang et al (33) reported the enhancement of I NCX by ␤-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, this augmentation was most likely due to the activation of I CFTR-Cl , which is also sensitive to Ni 2ϩ . Our results support previous studies (2,5,13,20) and a recent report of studies of rabbit ventricular cells by Ginsburg and Bers (11). Using guinea pig ventricular cells, Perchenet et al (25) and Zhang et al (33) reported the enhancement of I NCX by ␤-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…(30) also reported that PKA phosphorylated the Na ϩ /Ca 2ϩ exchange protein and increased I NCX by ϳ500% in control and by ϳ100% in failing ventricular cells from pig heart, suggesting that cardiac Na ϩ / Ca 2ϩ exchange is hyperphosphorylated in heart failure. To the contrary, no stimulatory effect of ␤-adrenergic receptor stimulation or PKA on exchange activity was detected in giant membrane patches excised from blebs of guinea pig ventricular cells (5), vesicle preparations of rat hearts (2), guinea pig ventricular cells (20), or BHK cells expressing the dog cardiac NCX1 (13).…”
mentioning
confidence: 99%
“…While some have observed increased NCX current after treatment with PKA activators (26,33,44), others have not observed any change (9,20,21). We were unable to detect PKA-dependent phosphorylation of the full-length NCX1 protein and suggest that the discrepancy between previous functional studies likely results from experimental differences in ionic homeostasis.…”
Section: Discussioncontrasting
confidence: 71%
“…Inorganic Cations (Colvin et al, 2000), and Ni 2ϩ (Kimura et al, 1987) , and Cd 2ϩ , may also function as substrates for the exchanger (Iwamoto and Shigekawa, 1998b). Among these divalent cations, Ni 2ϩ is the element most commonly used for blocking NCX activity during electrophysiological measurements (Fujioka et al, 1998;Main et al, 1997). The use of Ni 2ϩ as a NCX inhibitor is limited because its blocking concentrations are in the order of 2 to 5 mM, levels at which Ni 2ϩ is also able to inhibit other membrane currents (Iwamoto and Shigekawa, 1998b).…”
Section: Inhibitorsmentioning
confidence: 99%